ANALISIS PEST : KAJIAN PADA CRUDE PALM OIL INDONESIA - Widyaningtyas, Dian (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2024)
Palm Oil is an important commodity and has a strategic role in the Indonesian economy. Palm oil derivative products have a good prospect. The utilization of palm oil is widely used as a basic ingredient of medicines and healthcare industry. The previous research showed Revealed Comparative Advantage (RCA) index of palm oil Indonesia above 1. RCA> 1 indicates this product has competitiveness, but it’s still needs to be improved. This study analyzes the condition of macro environment that influences the development of palm oil derivative products. Politic, Economics, Social, and Technology (PEST) analysis can provide a broad picture of the influence of external factors that are important for palm oil. The PEST analysis results show that political, economic, and social impacts have a high impact on the palm oil industry, while technology has a moderate impact. The high impact of the economic and social conditions on macro environment are some great opportunities for further development. Seeing this, it is necessary to concentrate on one major segment and sharpen its as a strategy.